Efficacy and safety of mono antiplatelet therapy with colchicine in acute coronary syndrome patients following percutaneous coronary intervention: rationale and design of the MACT II trial - Jang, Ji Yong; Suh, Yongsung; Kim, Choongki; Byoun, Jeong Tae; Yun, Kyeong Ho; Lee, Jung-Hee; Jeon, Ki-Hyun; Cho, Sungsoo; Yoon, Hyuk-Joon; Kim, Jin Won; Lee, Bom; Kang, Se Hun; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionEarly discontinuation of aspirin after percutaneous coronary intervention (PCI) reduces bleeding risk, while inflammation-targeted strategies may offer additional benefit in patients with acute coronary syndrome (ACS). Residual inflammatory risk—reflected by persistently elevated high-sensitivity C-reactive protein (hs-CRP) levels—remains a significant contributor to adverse cardiovascular outcomes despite guideline-directed therapy. Colchicine has emerged as a potential anti-inflammatory agent in this context, but its optimal use remains uncertain.Methods and analysisMACT (Mono Antiplatelet and Colchicine Therapy) II is an investigator-initiated, prospective, multicenter, single-arm study designed to evaluate the safety and efficacy of an aspirin-free, inflammation-guided treatment strategy in 490 patients with troponin-positive ACS or ST-segment elevation myocardial infarction undergoing PCI with a sirolimus-eluting stent. Aspirin is discontinued on the day after PCI, and ticagrelor is continued at the standard dose. Colchicine (0.6 mg once daily) is initiated within 24 h after PCI. At 1 month, colchicine is continued or discontinued based on hs-CRP levels. The primary outcome is the 12-month incidence of net adverse clinical events, a composite of cardiovascular death, nonfatal myocardial infarction, nonfatal ischemic stroke, unplanned urgent revascularization, and major bleeding (Bleeding Academic Research Consortium type 3 or 5). Secondary outcomes include longitudinal hs-CRP trends, platelet reactivity, and adverse drug reactions.ConclusionsMACT II evaluates an aspirin-free, inflammation-guided treatment strategy in patients with ACS undergoing PCI. Colchicine therapy is initiated early during the acute phase of ACS and continued or discontinued based on inflammatory response as measured by hs-CRP. By tailoring treatment duration in this manner, the trial aims to reduce both ischemic and bleeding risks while avoiding unnecessary drug exposure. The findings may inform personalized anti-inflammatory strategies in contemporary clinical practice.Trial registrationClinicalTrials.gov Identifier: NCT06543082.